2009
DOI: 10.1177/073989130900600206
|View full text |Cite
|
Sign up to set email alerts
|

Leading Ministry Teams, Part II: Research on Effective Teams with Implications for Ministry Team Leadership

Abstract: To date, the major research efforts on teams and teamwork are found solely in the publicatications of Larson and LaFasto (1989, 2001) as well as those of Katzenbach and Smith (1993, 2001). This article reviews their major findings and continued research in the last 20 years. Research on effective ministry teams in Christian ministry contexts shows a number of common elements that affirmed both Larson and LaFasto's eight characteristics of effective teams and Katzenbach and Smith's description of effective grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…They suggested that “groups rely on the sum of ‘individual bests’ for their performance, but pursue no collective work products requiring joint effort” (p. 85). Those in ministry leadership must make a clear determination regarding this distinguishing point, which divides independent individuals collected in “groups” from integrated individuals cooperating as “teams.” “To team or not to team, that is the question” (Lawson & Eguizabal, 2009, p. 274). Simply renaming an existing collection of people a “team” and expecting improved results without modifying any of their processes or practices is akin to calling a fish a bird and expecting flight.…”
Section: The Power Of Definition – Team Vs Groupmentioning
confidence: 99%
“…They suggested that “groups rely on the sum of ‘individual bests’ for their performance, but pursue no collective work products requiring joint effort” (p. 85). Those in ministry leadership must make a clear determination regarding this distinguishing point, which divides independent individuals collected in “groups” from integrated individuals cooperating as “teams.” “To team or not to team, that is the question” (Lawson & Eguizabal, 2009, p. 274). Simply renaming an existing collection of people a “team” and expecting improved results without modifying any of their processes or practices is akin to calling a fish a bird and expecting flight.…”
Section: The Power Of Definition – Team Vs Groupmentioning
confidence: 99%